Elaboración de material didáctico de estimulación temprana para desarrollar la motricidad gruesa en niños y niñas menores de 2 años del centro de desarrollo del buen vivir “casita de chocolate” provincia de Cotopaxi, cantón Latacunga de la parroquia San Buenaventura en el período 2012-2013 - Martínez Herrera, Irma Verónica (2015)
The made research work contributes meaningful to relevant aspects inside the development in the process of gross motor abilities acquirement for the readiness of the psychomotor in the infants under 2 years old from Center of Buen Vivir “Casita de Chocolate”; through the implementation of didactic material based clearly in recreational activities and interaction with didactic materials. For applying the appropriate didactic material, we have seen fit to data collection by using the survey technique, taking into account the needs of the community mothers and exigencies of the community and society, it‟s essential that people who take care of children will be trained on everything that concerns to the theme hereof; as this benefits to the boys and girls under 2years old are participating in direct form in their learning because it is a manner of stimulating and motivating in order to achieve the right gross motor.